(untitled) (Colombia Medica, 2013)
The relevance/ and visibility of psychiatric disorders within the realm of medicine has significantly increased in recent times, possibly due to their high frequency and the negative impact they have on cost, disability and quality of life. The subjective nature of these disorders, their clinical complexity and the absence of reliable markers, keep us completely dependent on anamnesis and clinical examination. All of this, forces us, periodically, to review and refine diagnostic systems, hoping to improve the recognition and effective management of mental disorders. The scientific progress in basic neuroscience, observed during and following the “decade of the brain”, coupled with a lack of satisfaction with the existing system (DSM-IV) suggested it was the moment to embark in this task, hence the process leading to DSM-5.